Authentic Leadership and Whistleblowing: The Mediating Roles of Trust and Moral Courage - Andrey Hasiholan Pulungan; Kadek Jenitha Ayunda Tirtaning Sari; Sri Maharsi; Albert Hasudungan (Universitas Swadaya Gunung Jati, 2021)
AbstractStudies have shown that internal whistleblowing is an effective way to reduce unethical behavior and fraud risk in organizations. This study aims to empirically examine the mediating effects of affective trust and moral courage on the relationship between authentic leadership and employees internal whistleblowing intention. A convenience sampling method was utilized because the respondents were specific and there was no available public information about them. The survey was sent online to respondents who worked in a private company in Indonesia that applied a whistleblowing policy. One hundred sixty-three responses were analyzed by using SMART PLS 3. The findings suggest that both affective trust and moral courage improve the effects of authentic leadership on their employees intention to report fraud through internal channels. A leader with authentic attributes promotes employees' trust in their leader and improves their moral courage so they are more willing to report fraud to internal parties, including their leaders. Hence, this research demonstrates the significance of a good control environment in companies.Keywords: Affective trust; Authentic leadership; Internal whistleblowing intentions; Moral courage.Abstrak Studi telah menunjukkan bahwa pelaporan pelanggaran secara internal merupakan cara yang efektif untuk mengurangi perilaku tidak etis dan risiko kecurangan di dalam organasisasi. Penelitian ini bertujuan untuk menguji secara empiris pengaruh mediasi kepercayaan afektif dan keberanian moral terhadap hubungan antara kepemimpinan otentik dengan intensi pegawai melakukan pelaporan pelanggaran secara internal. Metode sampel convenience digunakan oleh karena responden yang spesifik dan ketiadaan informasi publik mengenai mereka. Survei dikirimkan secara online kepada responden yang bekerja di sebuah perusahaan swasta di Indonesia yang telah menerapkan kebijakan pelaporan pelanggaran. Seratus enam puluh tiga respon dianalisa dengan menggunakan SMART PLS 3. Hasil penelitian menunjukkan bahwa baik kepercayaan afektif maupun keberanian moral meningkatkan pengaruh kepemimpinan otentik terhadap untensi pegawai melaporkan kecurangan melalui jalur internal. Seorang pemimpin yang memiliki atribut otentik meningkatkan kepercayaan pegawai kepada pimpinan dan keberanian moral pegawai sehingga pegawai lebih mau melaporkan kecurangan kepada pihak-pihak internal, termasuk pimpinan mereka. Oleh sebab itu, penelitian menunjukkan pentingnya lingkungan pengendalian yang baik di dalam perusahaan.Katakunci: Intensi pelaporan pelanggaran secara internal; keberanian moral; kepercayaan afektif; kepemimpinan otentik.